2018
DOI: 10.18632/oncotarget.25733
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram reduces metastatic osteosarcoma tumor burden in an immunocompetent Balb/c or-thotopic mouse model

Abstract: IntroductionThe overall survival rate of patients with osteosarcoma (OS) and pulmonary metastases has remained stagnant at 15–30% for several decades. Disulfiram (DSF) is an FDA-approved aldehyde dehydrogenase inhibitor that reduces the metastatic phenotype of OS cells in vitro. Here we evaluate its in vivo efficacy, as compared to doxorubicin chemotherapy, in a previously-validated orthotopic model of metastatic OS.ResultsAll treatment groups displayed a significantly reduced quantitative OS metastatic burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…After approval by the University of Pittsburgh Institutional Animal Care and Use Committee (IACUC Protocol# 16119548), fifty 6-week-old immunocompetent Balb/c female mice received left proximal tibia paraphyseal injections of 5 × 10 5 K7M2 murine OS cells, as has been previously described 15,18. Mice were then prospectively separated into two groups ( n = 25 each): (1) ICG-assisted surgical resection; and (2) no ICG-assisted resection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After approval by the University of Pittsburgh Institutional Animal Care and Use Committee (IACUC Protocol# 16119548), fifty 6-week-old immunocompetent Balb/c female mice received left proximal tibia paraphyseal injections of 5 × 10 5 K7M2 murine OS cells, as has been previously described 15,18. Mice were then prospectively separated into two groups ( n = 25 each): (1) ICG-assisted surgical resection; and (2) no ICG-assisted resection.…”
Section: Methodsmentioning
confidence: 99%
“…All ICG measurements were performed using the SPY-Elite System (Stryker Corporation, Kalamazoo, MI, USA) as previously described. The timing and dosage of ICG administration was also based on our previous work 15,18. Surgical resections in group 1 were performed under the direct guidance of ICG–infrared imaging until there was no longer any fluorescent signal in the remaining hind limb (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Despite decades of ingenuity and investigation, the prognosis for a patient with metastatic osteosarcoma remains similar to that described by Meyers et al in 1993 [ 2 ], and the prognosis still depends in large part on the ability to surgically eradicate all evidence of disease. In this context, the study by Crasto et al [ 3 ] is a reason for renewed enthusiasm. Cancer stem cells (CSCs) represent a subpopulation of tumor cells that are thought to promote tumorigenesis.…”
mentioning
confidence: 99%
“…Elevated aldehyde dehydrogenase (ALDH) activity is associated with CSCs in both solid tumors and hematologic malignancies and has been similarly implicated in chemoresistance and tumorigenesis. Crasto et al [ 3 ] used disulfiram as an ALDH inhibitor to target the CSC subpopulation in a murine osteosarcoma model. The authors showed a reduction in metastatic tumor burden after treatment with disulfiram, which was comparable to that achieved with doxorubicin chemotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation